The study of the actuality, characteristic, object, and solution of elite sports in China's schools - Sun, Q.-L.; Gu, S.-Y. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
In order to make elite sports in China's schools to further develop, training mode should be improved. Scientific training should be adjusted to be adapted to increasingly hard competition. Conclusion and suggestion: The development of elite sports must have enough reserve. So, excellent athletes should be cultivated through many means and channels. Especially, the combination of school and palestra, the cooperation of school and enterprise and the pyramidal and longitudinal training mode of from elementary schools to middle schools to universities should be strengthened. The core of enhancing elite sport performance is scientific training and improving intellectual and capability structures. So, the monitoring of these factors should be especially strengthened.